Exploring the Diverse Etiological Landscape of epileptic Seizures in the adults admitted in tertiary care centre: A cross-sectional study - Verma, Archana; Mishra, Ashutosh; Kumar, Alok; Upadhayay, Sachin (Nepal Journal of Neuroscience, 2024)
Introduction: The knowledge of etiological spectrum of adult-onset seizures is important because of their frequent association with secondary causes. The present study was designed to explore the clinical and etiological spectrum of seizures in adults admitted to a tertiary care centre.Materials and Methods: We conducted a cross-sectional, hospital-based study on the adult patients admitted to a tertiary care centre with seizures from June 2022 to February 2024.Results: The mean age of the study population was 37.2 ± 7.7 years (range: 18–86 years), and 65.4% (68) of cases were men. The most common seizure type was focal to bilateral tonic- clonic seizure in 61.5% (64) of cases. Among them, 50% (52) were of acute symptomatic seizures, 38.8% (32) cases were of convulsive status epilepticus (CSE), and 19% (20) cases were of epilepsy. Amid the CSE cases, 56.2% (18) cases presented with new-onset CSE. Overall, the most common etiologies in adults were CNS infection in 52% (54), stroke in 17.3% (18), and post-traumatic 11.5% (12), followed by metabolic causes in 7.7% (8) of cases.Conclusion: Acute-symptomatic seizures and CSE in adults’ patients were found to be mostly related to CNS infections and strokes. The present study highlights the significance of promptly identifying and addressing these underlying disorders.